Impact of Cardiovascular-Kidney-Metabolic Syndrome on Quality of Life: Current Perspectives and Future Directions - Bharath, Gavini Siva; Tella, Jai Divya; Uppalapati, Mohan Chandu; Nadendla, Rama Rao; Rao, K.R.S. Sambasiva (Journal of Pharmacy Practice and Community Medicine)
Cardiovascular-Kidney-Metabolic Syndrome (CKMS) is a multifaceted condition involving cardiovascular disease, chronic kidney disease, and metabolic disorders such as diabetes, hypertension, and obesity, significantly impacting the Quality of Life (QoL) of those affected. This review delves into the comprehensive effects of CKMS on QoL, emphasizing the physical, psychological, and social challenges faced by patients. Physically, CKMS manifests through symptoms like fatigue, dyspnea, pain, and reduced physical activity, impairing functional capacity and daily living. Psychologically, individuals with CKMS often experience depression, anxiety, and cognitive impairments, which further diminish QoL. Socially, CKMS leads to isolation, increased caregiver stress, and substantial economic burdens due to the complexities of managing multiple chronic conditions. Current strategies to enhance QoL in CKMS involve a multidisciplinary approach, including patient education, psychosocial support, and lifestyle modifications. Pharmacological treatments are essential for managing the underlying conditions, yet continuous research is necessary to refine these therapies and optimize patient outcomes. Future directions for improving QoL in CKMS focus on precision medicine, leveraging technology-driven interventions, and integrated care models that address both medical and psychosocial needs comprehensively. Ultimately, a holistic, patient-centered approach is critical to mitigating the adverse effects of CKMS on QoL and enhancing the overall well-being of affected individuals. Addressing CKMS requires a collaborative effort among healthcare providers, patients, and policymakers to develop and implement effective strategies that improve the lives of those living with this challenging condition.
Keywords: Cardiovascular; Impact on patient care; Interplay; Kidney; Metabolic Syndrome; Multidisciplinary Care; Quality of life; Well-being